KETERAMPILAN DAN KECAKAPAN HIDUP (LIFE SKILL) : SEBUAH PERSOALAN MARTLABAT MANUSIA - Sarbiran Sarbiran (Jurnal Cakrawala Pendidikan, 2002)
There are relations between life skills and human dignityand existence because in human beings there are multiple intelligences,i.e., linguistic, spatial, artistic, psychomotoric, mathematical,interpersonai, intraperspnal, spiritual (religious), and emotionalintelligences. Therefore, there are also relations betweenlife skills and occupations that students have interest in and planto take up. It follows then that any development or improvementof iife skills in students necessitates an i~nderstmdingo f vocationalskills and vocational education since it is the mission ofvocational education to prepare students with the ability to workat ssmethng. So the educational process and traicing need toemphasize and pay attention to the multiple intelligencespossessed by students and simultaneously pay attention to thehidden curriculum that should be delivered. An improvementof students' life skills necessitates a new policy promoting inteachers an understanding of students' multiple intelligences,enough care in teaching, educating, and training, and adequatesense of responsibility.